International Society of Urological Pathology (ISUP) Consensus Conference on Current Issues in Bladder Cancer. Working Group 1: Comparison of Bladder Cancer Grading System Performance. - Downes, Michelle R.; Hartmann, Arndt; Shen, Steven; Tsuzuki, Toyonori; van Rhijn, Bas W. G.; Bubendorf, Lukas; van der Kwast, Theodorus H.; Cheng, Liang (American Journal of Surgical Pathology, 2024)
Grade is a key prognostic factor in determining progression in nonmuscle invasive papillary urothelial carcinomas. The 2 most common grading methods in use worldwide are the World Health Organization (WHO) 2004 and 1973 schemes. The International Society of Urological Pathology (ISUP) organized the 2022 consensus conference in Basel, Switzerland on current issues in bladder cancer and tasked working group 1 to make recommendations for future iterations of bladder cancer grading. For this purpose, the ISUP developed in collaboration with the European Association of Urology a 10-question survey for their memberships to understand the current use of grading schemes by pathologists and urologists and to ascertain the areas of potential improvements. An additional survey was circulated to the ISUP membership for their opinion on interobserver variability in grading, reporting of urine cytology, and challenges encountered in grade assignment. Comprehensive literature reviews were performed on bladder cancer grading prognosis and interobserver variability along with The Paris System for urine cytology. There are notable differences in practice patterns between North American and European pathologists in terms of used grading scheme and diagnosis of papillary urothelial neoplasm of low malignant potential. Areas of common ground include difficulty in grade assignment, a desire to improve grading criteria, and a move towards subclassifying high-grade urothelial carcinomas. The surveys and in-person voting demonstrated a strong preference to refine current grading into a 3-tier scheme with the division of WHO 2004 high grade into clinically relevant categories. More variable opinions were voiced regarding the use of papillary urothelial carcinoma with low malignant potential.
EVALuna2:540670